2014
DOI: 10.1161/strokeaha.113.003537
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Priming Accelerates Recovery of Upper Limb Function After Stroke

Abstract: Background and Purpose— The ability to live independently after stroke depends on the recovery of upper limb function. We hypothesized that bilateral priming with active–passive movements before upper limb physiotherapy would promote rebalancing of corticomotor excitability and would accelerate upper limb recovery at the subacute stage. Methods— A single-center randomized controlled trial of bilateral priming was conducted with 57 patients randomized at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
106
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(113 citation statements)
references
References 19 publications
2
106
1
Order By: Relevance
“…However, they may produce similar effects that may include increased excitability or normalization of inhibition, which coincide with improvements in motor behavior. 13 Methods of priming the motor cortex that are most relevant to rehabilitation include: (1) stimulation-based priming; 14-22 (2) motor imagery and action observation; 23-28 (3) manipulation of sensory input; 29-31 (4) movement-based priming; 7, 32-36 and (5) pharmacology-based priming. 37 Studies examining priming for the primary motor cortex (M1) are increasing in number.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they may produce similar effects that may include increased excitability or normalization of inhibition, which coincide with improvements in motor behavior. 13 Methods of priming the motor cortex that are most relevant to rehabilitation include: (1) stimulation-based priming; 14-22 (2) motor imagery and action observation; 23-28 (3) manipulation of sensory input; 29-31 (4) movement-based priming; 7, 32-36 and (5) pharmacology-based priming. 37 Studies examining priming for the primary motor cortex (M1) are increasing in number.…”
Section: Introductionmentioning
confidence: 99%
“…32-35 In neurologically healthy subjects, mirror-symmetric movements, but not alternating movements, were associated with improvements in motor performance and interhemispheric disinhibition. 7 Active-passive bilateral therapy (also known as bilateral priming) uses a low-tech device known as “the rocker” which was first described by Stinear and Byblow.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms that mediate the effects of bilateral intervention in subjects with stroke include rebalancing interhemispheric inhibition,20, 21, 22 activating the homologous neural networks in both hemispheres,23, 24 and recruiting the neural networks of the contralesional hemisphere 17, 23, 25. The use of transcranial magnetic stimulation in subjects with stroke, in which the maximum voluntary contraction of the nonparetic hand was combined with less‐forceful contraction of the paretic hand, increased the cortical excitability of the ipsilesional motor representation area of the hand when compared with contraction of the paretic hand alone 24.…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence shows that bilateral intervention recruits spare neural substrates to enhance motor recovery17, 20, 21, 22, 23, 24, 25; we thus hypothesized that the application of TENS over both paretic and nonparetic legs (Bi‐TENS) might induce greater and earlier improvement in lower‐limb motor function than the use of Uni‐TENS in subjects with stroke. A literature search revealed that no study has compared the efficacy of Bi‐TENS+TOT and Uni‐TENS+TOT on motor recovery after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Second, there are a number of experimental approaches under investigation which aim to increase the effects of training by enhancing the potential for use-dependent plasticity. These ‘primers’ of the motor system might include drugs (eg, fluoxetine2), specific forms of activity (active–passive bilateral arm training,3 aerobic exercise4) and non-invasive brain stimulation (eg, transcranial direct current stimulation, tDCS5 6). None of these interventions should be thought of as treatments, but rather as tools for enhancing the effects of conventional practice-based treatment, which in the case of post-stroke motor impairment is currently physical therapy.…”
mentioning
confidence: 99%